Anterior pituitary weight, cAMP, cGMP and prolactin levels after combined treatment with estradiol and methylene blue - Schreiber, V; Nedvídková, J; Jahodová, J (Physiological research, 1993)
Male rats received estradiol benzoate in a long acting microcrystalline suspension (1 mg/rat i.m., twice a week), methylene blue (MB) 0.5% in the food and the combination of estradiol and MB. After three weeks, MB partially inhibited the growth response of the anterior pituitary to estradiol and it partially inhibited the increase of cAMP content in anterior pituitary. The increase of anterior pituitary cGMP content was not modified by MB, neither the ratio cAMP/cGMP in the anterior pituitary which, however, decreased after estradiol. This decrease was not modified by MB. On the other hand, the prolactin (PRL) increase in the blood after estradiol was inhibited by MB, although the prolactin content in the anterior pituitary was not. Methylene blue alone did not change blood prolactin concentration, but it unexpectedly elevated blood thyroxine levels and this effect was partially inhibited by simultaneous estradiol treatment.
Keywords: AMP cyklický; velikost orgánu; lékové interakce; estradiol; methylenová modř; krysa rodu Rattus; Cyclic GMP; zvířata; prolaktin; Cyclic AMP; Methylene Blue; potkani Wistar; Drug Interactions; Prolactin; Pituitary Gland, Anterior; Estradiol; Rats, Wistar; Male; adenohypofýza; guanosinmonofosfát cyklický; Rats; Animals; Organ Size; mužské pohlaví